2022
DOI: 10.1111/ans.17983
|View full text |Cite
|
Sign up to set email alerts
|

Mayo adhesive probability score is associated with perioperative outcomes in retroperitoneal laparoscopic adrenalectomy

Abstract: Backgrounds This study aimed to determine whether the Mayo adhesive probability score (MAP), which evaluated adherent perinephric fat (APF), is useful in evaluating the difficulty of retroperitoneal laparoscopic adrenalectomy (RLA), and to analyse the correlation between MAP and perioperative parameters. Methods Clinical data of 104 patients with adrenal adenoma who underwent RLA were collected for retrospective analysis. According to the CT images obtained before surgery, patients were divided into two groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…In the same year, Chen et al studied the perioperative outcomes of retroperitoneal LA and recognized MAP as the only factor affecting independently all of the evaluated outcomes (operation time, blood loss, hemoglobin drop) [16]. MAP score was also used by the investigators of a third study to evaluate the factors affecting operation time in retroperitoneal LA [17]. MAP score and tumor size were independent parameters of extended procedure duration.…”
Section: Discussionmentioning
confidence: 99%
“…In the same year, Chen et al studied the perioperative outcomes of retroperitoneal LA and recognized MAP as the only factor affecting independently all of the evaluated outcomes (operation time, blood loss, hemoglobin drop) [16]. MAP score was also used by the investigators of a third study to evaluate the factors affecting operation time in retroperitoneal LA [17]. MAP score and tumor size were independent parameters of extended procedure duration.…”
Section: Discussionmentioning
confidence: 99%
“…In total, ten eligible retrospective studies [10][11][12][13][14][15][16][17][18][19] including 3200 patients (1320 patients in high MAP group and 1880 patients in low MAP group) undergoing PN, DN or LA were included. The 10 studies from six countries were published between 2018 and 2022.…”
Section: Study Characteristics and Quality Assessmentmentioning
confidence: 99%
“…Increasing evidence demonstrated that MAP score is a credible and accurate predictor of APF in partial nephrectomy (PN) [4][5][6][7][8] and donor nephrectomy (DN) [9,10]. Recent studies reported that MAP score is associated with perioperative outcomes in PN [11][12][13][14], DN [10,15,16], and Laparoscopic Adrenalectomy(LA) [17][18][19], however, the conclusion among above studies is controversial. Thus, this meta-analysis aimed to explore clinical predictive role of MAP score in patients undergoing PN, DN, and LA.…”
Section: Introductionmentioning
confidence: 99%
“…[13] A higher MAP score was associated with the operative time in LA [14,15] , as well as estimated blood loss and drainage tube removal time. [15] It was evident that high BMI or high MAP score affected LA, but which speci c aspects of the surgery were affected and whether MTRLA truly overcomed this challenge remains to be determined. We propose a new concept called adhesive periadrenal fat (APAF) [16] , which is de ned as the presence of image-dense stranding in periadrenal fat, either in the form of thin bars or thick bands.…”
mentioning
confidence: 92%